Taxonomy of the leafy vegetables in Bangladesh - Khatun, Maksuda; Hassan, Md. Abul; Islam, Shaikh Nazrul; Rahman, M. Oliur (Bangladesh Journal of Plant Taxonomy, 2013)
Thirty four exploration trips made throughout Bangladesh from 2000 to 2012 resulted in identification of 186 taxa used as leafy vegetables in the country, of which 173 taxa belong to angiosperms and 13 taxa to pteridophytes. Among the angiosperms, Magnoliopsida is represented by 153 taxa under 114 genera and 43 families, whereas Liliopsida is represented by 20 species under 15 genera and 8 families. Pteridophytes are symbolized by 13 species belonging to 10 genera and 10 families. Under each taxon updated nomenclature, vernacular names, habit, representative specimen and area of major consumption of the plant as a leafy vegetable have been provided. Out of 186 leafy vegetables identified in Bangladesh, 140 taxa are wild and 46 are cultivated. Among the cultivated ones 16 species are cultivated only as leafy vegetables and 30 are cultivated for other purposes but also used as leafy vegetables. A total of 61 species have been newly documented as leafy vegetables for Bangladesh. DOI: http://dx.doi.org/10.3329/bjpt.v20i1.15469 Bangladesh J. Plant Taxon. 20(1): 95-123, 2013 (June)